Carbon Monoxide Inhibits Tenascin-C Mediated Inflammation via IL-10 Expression in a Septic Mouse Model - Md. Jamal Uddin; Chun-shi Li; Yeonsoo Joe; Yingqing Chen; Qinggao Zhang; Stefan W. Ryter; Hun Taeg Chung (Mediators of Inflammation)
Tenascin-C (TN-C), an extracellular matrix (ECM) glycoprotein, is specifically induced upon tissue injury and infection and during septic conditions. Carbon monoxide (CO) gas is known to exert various anti-inflammatory effects in various inflammatory diseases. However, the mechanisms underlying the effect of CO on TN-C-mediated inflammation are unknown. In the present study, we found that treatment with LPS significantly enhanced TN-C expression in macrophages. CO gas, or treatment with the CO-donor compound, CORM-2, dramatically reduced LPS-induced expression of TN-C and proinflammatory cytokines while significantly increased the expression of IL-10. Treatment with TN-C siRNA significantly suppressed the effects of LPS on proinflammatory cytokines production. TN-C siRNA did not affect the CORM-2-dependent increase of IL-10 expression. In cells transfected with IL-10 siRNA, CORM-2 had no effect on the LPS-induced expression of TN-C and its downstream cytokines. These data suggest that IL-10 mediates the inhibitory effect of CO on TN-C and the downstream production of proinflammatory cytokines. Additionally, administration of CORM-2 dramatically reduced LPS-induced TN-C and proinflammatory cytokines production while expression of IL-10 was significantly increased. In conclusion, CO regulated IL-10 expression and thus inhibited TN-C-mediated inflammation in vitro and in vivo.